2020
DOI: 10.1111/1751-7915.13524
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota and its interactions with cardiovascular disease

Abstract: Summary The intestine is colonized by a considerable community of microorganisms that cohabits within the host and plays a critical role in maintaining host homeostasis. Recently, accumulating evidence has revealed that the gut microbial ecology plays a pivotal role in the occurrence and development of cardiovascular disease (CVD). Moreover, the effects of imbalances in microbe–host interactions on homeostasis can lead to the progression of CVD. Alterations in the composition of gut flora and disruptions in gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(82 citation statements)
references
References 189 publications
(218 reference statements)
1
79
0
2
Order By: Relevance
“…ere are nearly 10 14 microbes in the human body, approximately 10 times the number of human cells, and the impact of the gut microbiota on human health and disease has attracted increasing scientific interest [25][26][27][28] in recent years, including in areas such as obesity, inflammatory diseases, cardiovascular diseases, and tumors. e gut microbiota is believed to be involved in the pathologic process of EMs [29].…”
Section: Discussionmentioning
confidence: 99%
“…ere are nearly 10 14 microbes in the human body, approximately 10 times the number of human cells, and the impact of the gut microbiota on human health and disease has attracted increasing scientific interest [25][26][27][28] in recent years, including in areas such as obesity, inflammatory diseases, cardiovascular diseases, and tumors. e gut microbiota is believed to be involved in the pathologic process of EMs [29].…”
Section: Discussionmentioning
confidence: 99%
“…When the balance of the gut microbiota is disturbed due to certain factors, the body may suffer from diseases such as obesity, diabetes, or even cancers (such as colorectal cancer). 6 , 7 Accumulative research proposes that the gut microbiota is closely related to the regulation of bone metabolism, although its related mechanism has not been fully discovered. The rapid development of modern molecular biotechnology has facilitated the continuous discovery of the human microbiome, and may provide more information on early events about the pathogenesis of OP.…”
Section: Introductionmentioning
confidence: 99%
“…As stated earlier, studies have shown that EHS disrupts the gastrointestinal barrier, leading to leakage of gut microbiota and its accompanying metabolites into the circulatory system [26]. Despite playing a proatherogenic role in IHD, elevated TMAO contributes to myocardial fibrosis, ventricular remodeling and dysfunction [39,40] . Further, TMAO levels are strongly associated with major adverse cardiovascular events in HF patients [41] .…”
Section: Delayed Heart Failure In Heatstroke Patientsmentioning
confidence: 89%
“…Another possible mechanism of HF in HS patients is the role of gut microbiota-derived metabolite TMAO [ 26 , 39 - 41 ]. In the EHS animal study, TMAO had a biphasic response, rising early (0.5 hours post-EHS) before returning to baseline at three days post-EHS and subsequently rising later over the 14 days [ 19 ]⁠.…”
Section: Reviewmentioning
confidence: 99%